ChemInform Abstract: Nanoparticles Made of π‐Conjugated Compounds Targeted for Chemical and Biological Applications. Issue 2 (23rd December 2015) - Xu, Xinjun; Liu, Ronghua; Li, Lidong
Abstract: Review: 125 refs.